Scientific explanation and systematics. Issue 3 (19th April 2021) - de Santis, Marcelo Domingos
Abstract : Cladists have pursued, by way of philosophy of science, specific guidelines for ways to make the discipline more "scientific". For that they incorporated the philosophy of Karl Popper to validate their research program. Kluge, for instance, urged the adoption of standards outlined by philosophers of science, like Hempel, for scientific explanation. In doing that, he used the covering law model of scientific explanation to the philosophy and theory of cladism. While widely known and discussed, this model is severely criticized by philosophers. A number of counter examples were developed, among them the "symmetry thesis", which has implications in evolutionary biology. Before scrutinize Hempel's model, I will show how Hennig regarded the issues of explanation and causality in systematics. After, I shall discuss how the cladists did the incorporation of the covering law model. I will argue its criticize each of the main claims made by Kluge in relation to the model itself and its applicability to systematics. I conclude that Hempel's (and Popper's) model has little to offer in the way of positive guidelines for constructing successful explanations in cladistics.